2007
DOI: 10.1002/cbf.1420
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxin III induces c‐jun N‐terminal kinase‐dependent apoptosis in HL‐60 human leukaemia cells

Abstract: Cardiotoxin III (CTX III), a basic polypeptide with 60 amino acid residues isolated from Naja naja atra venom, has been reported to have anticancer activity. The molecular effects of CTX III on HL-60 cells were dissected in the present study. We found that the antiproliferative action of CTX III on HL-60 cells was mediated through apoptosis, as characterized by an increase of sub G1 population, DNA fragmentation and poly(ADP-ribose) polymerase (PARP) cleavage. Upregulation of Bax, downregulation of Bcl-2, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 25 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…To further confirm apoptosis in 4βHWE-induced H1299 cells, annexin V and PI double-staining (Pharmingen, San Diego, CA) was performed as described before [30]. In brief, 1 × 10 6 cells per 100-mm Petri-dish (at 70%~80% confluency) were treated with vehicle or 51 μg/mL of 4βHWE for 24 h. Subsequently, cells were labeled with annexin V-FITC (10 μg/mL)/PI (10 μg/mL); stained slides were mounted, and analyzed using an inverted fluorescence microscope (TE2000-U; Nikon).…”
Section: Methodsmentioning
confidence: 99%
“…To further confirm apoptosis in 4βHWE-induced H1299 cells, annexin V and PI double-staining (Pharmingen, San Diego, CA) was performed as described before [30]. In brief, 1 × 10 6 cells per 100-mm Petri-dish (at 70%~80% confluency) were treated with vehicle or 51 μg/mL of 4βHWE for 24 h. Subsequently, cells were labeled with annexin V-FITC (10 μg/mL)/PI (10 μg/mL); stained slides were mounted, and analyzed using an inverted fluorescence microscope (TE2000-U; Nikon).…”
Section: Methodsmentioning
confidence: 99%
“…(PharMingen, San Diego, CA) was used as described (Chien et al, 2008). In brief, cells were treated with vehicle or 3.57 mM of protoapigenone in medium for 24 h. After exposure, the cells were labeled with Annexin V conjugated fluorescein isothiocyanate (Annexin V-FITC) (10 mg=mL) and PI (10 mg=mL).…”
Section: Lung Cancer Cell Killing By Protoapigenone 503mentioning
confidence: 99%
“…Cobra cardiotoxins (CTXs) show a wide range of biological activities including hemolysis, cardiotoxicity, and disruption of muscular integrity [1,2,3]. Moreover, accumulated evidence has shown that CTXs induce apoptosis in cancer cells through the mitochondria-mediated apoptotic pathway, lysosome-mediated death pathway, or membrane-damaging effects [4,5,6,7,8]. It is widely believed that the plasma membrane is a target of CTXs, but the membrane pore formed by CTXs may have a limited lifetime on the cell surface due to membrane reorganization [9].…”
Section: Introductionmentioning
confidence: 99%